2016
DOI: 10.1016/j.tiv.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

The presence of macrophages and inflammatory responses in an in vitro testicular co-culture model of male reproductive development enhance relevance to in vivo conditions

Abstract: Our 3-dimensional testis co-culture system (3D-TCS) represents a promising model of male reproductive toxicity which captures sensitive processes of male reproductive development and contains the main testes cell types (germ, Leydig and Sertoli cells). Macrophages are another cell type important for testicular function and help to modulate immuno-endocrine processes during testes development. Chemicals such as phthalate esters (PE’s) affect macrophage function and testosterone production in the testes in vivo.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 40 publications
4
8
0
Order By: Relevance
“…CXCL1 protein was indeed found to be upregulated in the testes of MEHP-treated rats. These findings are in agreement with other reports that phthalates (DBP and DEHP) can upregulate Cxcl1 and Cxcl10 gene expression in the testis in vivo (Lahousse et al , 2006; Johnson et al , 2007), and in an in vitro testicular co-culture model (Harris et al , 2016). How expression of CXCL1 is induced remains to be investigated, but TNFα and Il-1β are likely candidates, as they have been reported to induce CXCL1 expression in peritubular myoid cells (PTMCs) and SCs, respectively (Aubry et al , 2000), and we have previously shown both cytokines to be increased upon MEHP exposure (Stermer et al , 2017).…”
Section: Discussionsupporting
confidence: 93%
“…CXCL1 protein was indeed found to be upregulated in the testes of MEHP-treated rats. These findings are in agreement with other reports that phthalates (DBP and DEHP) can upregulate Cxcl1 and Cxcl10 gene expression in the testis in vivo (Lahousse et al , 2006; Johnson et al , 2007), and in an in vitro testicular co-culture model (Harris et al , 2016). How expression of CXCL1 is induced remains to be investigated, but TNFα and Il-1β are likely candidates, as they have been reported to induce CXCL1 expression in peritubular myoid cells (PTMCs) and SCs, respectively (Aubry et al , 2000), and we have previously shown both cytokines to be increased upon MEHP exposure (Stermer et al , 2017).…”
Section: Discussionsupporting
confidence: 93%
“…Immunohistochemical analyses of the inflammatory marker CD68 revealed an increased presence of macrophages in the interstitial areas of PND60 animals, suggesting a possible activation of the inflammatory pathway, which has been proposed to lead to fibrosis 27 . This result correlated well with our previous research on DEHP and inflammation in adipose tissue 48 and with other reports that describe proinflammatory effects of phthalates in the testes 49 51 . Interestingly at PND200 the effect was lost, suggesting that age-related changes in the testes affect susceptibility to DINCH.…”
Section: Discussionsupporting
confidence: 93%
“…Testicular interstitium contains several cell types, including Leydig cells, macrophages, and endothelial cells, capable of producing proinflammatory cytokines such as IL-1β, IL-6, and TNF-α to modulate testis functions (25)(26)(27)(28)(29). CCL2 is a chemokine expressed constitutively in testis by Leydig cells and peritubular cells (30,31).…”
Section: Introductionmentioning
confidence: 99%